Effects of thermal environment on cognitive response in sedentary activities. A short revision - Emília Quelhas da Costa (2012)
The study about the influence of the thermal environment on cognitive response is fundamental to understanding better the connection between the basic variables and cognitive performance. This also helps the better understanding of safety situation, guidance and decision-making, especially to avoid critical situations. The main objective of this work is to relate the physiological with cognitive response, trying to find exposure limits covering both occupational settings and social environments in high temperatures. For this purpose, was used a systematic cross-linked search, relating several key words and search phrases in different electronic data bases with different criteria. According to the survey results, it's clear the importance of studying the core temperature and the sweating rate to understand the relationship between the thermal environment and the cognitive response So, in this review, different topics are considered by different authors as fundamental for the study of thermal environment influence on cognitive response as: type of tasks, dehydration, brain, skin and core and temperature. It was concluded in relation to sedentary activities that the results are still questionable. However, this brief survey indicates that the cognitive response is affected by, at least, four parameters, core temperature, dehydration, psychological factors and the type of the tasks.